The influence of children’s physical activity time on the development of prosocial moral reasoning: evidence from school consolidation policy in rural northern China - Zhao, Guo Dong; Bai, Zeya; Yin, Yiyuan; Yue, Wumin; Zhang, Tingting; Shi, Rui; Guo, Can (Frontiers in Psychology, 2025)
This study integrates TPSR model and Eisenberg’s theory of moral emotion as the theoretical framework to explore the influence of physical activity on prosocial moral reasoning of rural primary school students, focusing on the “school merger” policy. Data from 292 fifth and sixth-grade students in Ping Yao County were analyzed. Results showed significant correlations between physical activity frequency and prosocial moral reasoning, with physical activity negatively correlated with hedonistic tendencies and positively correlated with needs-oriented and other-oriented tendencies. Regression analysis indicated that physical activity predicted the variance in hedonistic moral reasoning (R2 = 0.184). The findings suggest that increased physical activity promotes moral reasoning development, particularly for boarders and younger students.